Evaluation of Anxiety-Induced Hemodynamics Response in Known Hypertensive Patients Undergoing Surgical Removal of Impacted Mandibular Third Molar Surgery: An Observational Study - E. S. Shobha; M. D Anagha; Vinod Rangan; Yashas N. Raj; Meghana Patil; B. K. Ramnarayan (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Hemodynamic parameters such as systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), and oxygen saturation (SpO2) are critical in evaluating cardiovascular stability during surgical procedures. Anxiety, a common psychological condition, has been linked to hemodynamic fluctuations, particularly in hypertensive patients. Materials and Methods: This observational study included 27 hypertensive patients scheduled for impacted third molar extraction under local anesthesia. Anxiety levels were assessed preoperatively using the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Hemodynamic parameters (SBP, DBP, HR, and SpO2) were measured preoperatively, intraoperatively, and postoperatively using a sphygmomanometer and pulse oximeter. Statistical analysis was conducted using the Wilcoxon signed rank test and Mann–Whitney test, with a significance threshold of P < 0.05. Results: A significant increase in HR was observed from preoperative (74.07 ± 3.78 bpm) to intraoperative (76.78 ± 6.08 bpm, P = 0.005), and from preoperative to postoperative (94.70 ± 3.75 bpm, P < 0.001). SpO2 levels significantly decreased from preoperative (94.89 ± 4.40%) to postoperative (75.70 ± 5.68%, P < 0.001). Although SBP increased intraoperatively (129.26 ± 7.21 mmHg) compared to preoperative levels (127.52 ± 10.08 mmHg), the difference was not statistically significant (P > 0.05). However, a significant decline in SBP was noted postoperatively (126.52 ± 7.91 mmHg, P = 0.006). No significant variations in DBP were recorded across time points (P > 0.05). Gender-based comparisons revealed no significant differences in anxiety scores (P > 0.05), except for postoperative HR, which was significantly higher in females (95.61 ± 2.99 bpm) compared to males (92.89 ± 4.59 bpm, P = 0.043). Conclusion: Anxiety significantly impacts HR and SpO2 levels in hypertensive patients undergoing impacted third molar extraction. Although SBP changes were significant postoperatively, DBP remained stable across time points.